A young woman with traumatic vertebral artery occlusion: a case report - Ghaffarzad, Amir (J Cardiovasc Thorac Res, 2018)
Vertebral artery occlusion (VAO) may result from closed head or neck trauma and can be lifethreatening due to brain-stem and cerebellar infarction. CT angiography is recommended as a screening diagnostic tool in selected patients after blunt cervical trauma. A 24-year-old woman was admitted to our emergency department with left hemiplegia two days after motor vehicle collision. Final diagnosis of occlusion of the right vertebral artery was made in CT angiography. She was treated with anticoagulant for 4 days then discharged with 5/5 muscle forces. She was advised to continue warfarin and atorvastatin for her after discharge.